Analisis Kepuasan Kerja Karyawan Melalui Faktor-Faktor Quality of Work Life (QWL) pada PT. Pertamina (Persero) Perkapalan - Kartika, Lindawati; Maarif, Syamsul (IPB University, 2011)
PT. Pertamina (Persero) Shipping as shipping division of PT. Pertamina (Persero) since 1959 is affecting by a new transformation strategy of PT. Pertamina, as holding, to face the oil and gas regulation - UU No. 22 year 2001, which change Indonesian oil market from monopoly into competitive market. As competitiveness strategy, the transformation is a necessary condition to achieve PT. Pertamina goal to be world class Oil Company. Employee commitments to service and performance quality are critical factors to achieve its goal, which human resources quality will be improved by providing employee satisfaction. The research objectives at PT. Pertamina (Persero) Shipping were (1) to identify the level of employee satisfaction, (2) to analyze the Quality of Work Life (QWL) , (3) to identify the factor of QWL which influence employee satisfaction, and (4) to identify the factors need to be improve to achieve employee satisfaction. The primary and secondary data were collected from the company. The primary data was collected using interviewed by likert scale questionnaires. And the research samples are 187 respondents which taken from 323 population of employee at PT. Pertamina (Persero) Shipping by cluster random sampling technique at 5% standard error, and analyzed by Structural Equation Modeling (SEM). The study showed employee satisfaction level is good, which indicated by 3,70 score of total value of turnover, absenteeism, age, job level and organization size and 3,63 score on average value of all QWL variables. The SEM analysis showed job satisfaction variables such as communication, safety and conflict resolutions are influencing QWL. Other QWL factors were identify to be improve, by order are health, career development, employee participation, adequate compensation, pride and job security.